2018
DOI: 10.1186/s13058-018-1009-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of exercise and/or reduced calorie dietary interventions on breast cancer-related endogenous sex hormones in healthy postmenopausal women

Abstract: BackgroundPhysical inactivity and being overweight are modifiable lifestyle risk factors that consistently have been associated with a higher risk of postmenopausal breast cancer in observational studies. One biologic hypothesis underlying this relationship may be via endogenous sex hormone levels. It is unclear if changes in dietary intake, physical activity, or both, are most effective in changing these hormone levels.ObjectiveThis systematic review and meta-analysis examines the effect of reduced caloric di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
30
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 31 publications
5
30
0
1
Order By: Relevance
“…A reduction in receptor expression results in the lack of cell stimulation by sex hormones, followed by cell apoptosis (17). We found statistically insignificant differences between the estradiol levels in PT vs. SC groups, in accordance with other authors (9,15,28).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…A reduction in receptor expression results in the lack of cell stimulation by sex hormones, followed by cell apoptosis (17). We found statistically insignificant differences between the estradiol levels in PT vs. SC groups, in accordance with other authors (9,15,28).…”
Section: Discussionsupporting
confidence: 91%
“…Many scientific reports indicate a protective effect of physical activity on breast cancer (8,9,13,(15)(16)(17), including in patients after comprehensive breast cancer treatment (8,9,(18)(19)(20)(21)(22)(23)(24). From the results of our study, we found two mechanisms which confirm these observations, namely desensitization of cells due to reduced expression of ER and PR, as well as increased apoptosis which positively correlated with the level of training intensity.…”
Section: Discussionsupporting
confidence: 85%
“…Furthermore, randomized clinical trials testing the effects of physical activity on biomarkers of cancer, as well as animal models, have provided important mechanistic information to support the relationship between physical activity and reduced cancer risk. (66)(67)(68)(69) For cancer survival, the PAGAC identified several research needs. Because of the increasing length of cancer survivorship, there is need to continue long-term follow-up of cohorts of cancer survivors, with repeated self-report and device-based measures of physical activity, to determine long-term associations of physical activity with recurrence and survival.…”
Section: Discussionmentioning
confidence: 99%
“…18 This and other diabetes prevention studies found sustained and long-term benefits including a reduction in the cumulative incidence of diabetes, and lower fasting glucose levels, even after intervention activities ceased. [18][19][20] Beneficial changes in circulating sex steroid hormones with weight loss have been observed in shorter-term randomized clinical trials of exercise or dietary weight loss, and are principally attributed to reductions in adiposity, [21][22][23][24][25][26] including the 12-month results in our study. 7 An ancillary study nested within the Diabetes Prevention Program (DPP) reported that reductions in visceral and subcutaneous adipose tissue in overweight glucose intolerant participants, were independently associated with significant increases in in SHBG and estrone in postmenopausal women.…”
Section: Discussionmentioning
confidence: 82%